Keris Cirebon: Suatu Penelusuran Awal - Tendi, Tendi (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Keris is a sharp weapon that has long been recognized by the people of the archipelago, including Cirebon. There are many claims about the identity of the Cirebon kris, although its characteristics remain vague. This study seeks to unravel the mystery that still surrounds the Cirebon kris tradition and explain matters related to the unique weapon-shaped heirloom. The method used in this study is the historical method with a qualitative research approach with its emphasis as part of cultural studies. Through this research, it is known that: 1) Keris is a typical weapon of the archipelago that has undergone evolution for a long time; 2) As a region located in the northern coastal region of Java, Cirebon has a dynamic kris treasure; 3) Two legendary krises of Cirebon, Keris Ki Kanta Naga and Keris Setan Kober, live in the oral tradition of the Cirebon community so that the truth about the claims of the two works of Cirebon craftsmanship, must be researched further; 4) In terms of philosophy, Cirebon krises have a deep meaning related to various socio-cultural aspects that are intertwined with other aspects of the life of the people of Cirebon.